Mobile online game experience and community interaction: Mechanisms affecting user satisfaction - Yong-Dong Shi; Hui-Xin Feng; Jiong Liu; Yun-Long Ma; Qi-Xiao (Acta Psychologica)
The study investigates the mechanisms by which mobile online game experience and community interaction influence user satisfaction from the perspective of perceived value. Utilizing a survey methodology, the study gathered 252 valid responses and employed structural equation modeling to test the research model. The findings reveal that both game experience and community interaction positively impact user satisfaction in mobile gaming contexts. i.e., 1) a high-quality game experience significantly enhances perceived entertainment value 2) robust community interaction not only increases perceived entertainment value, but also positively affects perceived social value, and 3) the enhanced perceived values, in turn, contribute to higher overall user satisfaction. Theoretically, the study makes several original contributions to the literature by enriching the body of knowledge on mobile online game user experience, particularly focusing on the mobile platform. By integrating game experience with community interaction, it demonstrates that mobile online game users derive both entertainment and social value from their interactions, contributing to research on virtual community interactions and customer experience theory. Furthermore, the study explores how the perceived value derived from community interactions impacts user satisfaction, extending the existing literature on perceived value. The findings provide practical insights for mobile game developers, offering guidance on enhancing player enjoyment and promoting sustained engagement. Practically, by emphasizing the importance of entertainment and social value throughout the game usage process, the study suggests strategies for mobile game companies to develop high-quality communities that foster increased user satisfaction and continuous user engagement. These insights are crucial for mobile game enterprises in crafting effective game development and marketing strategies, highlighting the necessity of addressing both entertainment and social aspects to create a comprehensive and engaging user experience, essential for maintaining long-term user interest and loyalty.